Potensi dan Pemanfaatan Air Sungai Seruwai di Desa Tanjung Rejo Kabupaten Deli Serdang - Nadia Harahap; Tumiar Tumiar (Jurnal Pendidikan Dirgantara, 2025)
This study aims to identify and analyze the potential and utilization of the Seruwai River in Tanjung Rejo Village, Deli Serdang Regency. As a natural resource, the river plays a vital role in supporting the lives of local communities in terms of social, economic, and environmental aspects. The research employed a descriptive qualitative method through observation, interviews, and literature review. The findings indicate that the Seruwai River is utilized by residents for various needs, including agricultural irrigation, freshwater fish farming, and fishing as a livelihood. The river also serves as a natural reservoir for rainwater. However, its utilization is not yet optimal due to water pollution caused by domestic waste, which affects water quality. Therefore, sustainable river management is necessary through cooperation between the local community and village authorities to preserve the river and improve the welfare of the residents.